CHARACTERIZATION AND PROSPECTIVE PROCESS OF MANGANESE ORE OF TANGGAMUS AND WAY KANAN REGENCY LAMPUNG PROVINCE - Mufakhir, Fika Rofiek; Sumardi, Slamet (Teknologi Indonesia, 2014)
Manganese (Mn) has a very important role in various industrial fields such as iron, steel, food, agriculture and chemical industry. High grade Mn ore(>40%) are generally processed through the pyrometallurgy process, whereas for low grade Mn ore (<40%) is processed through the hydrometallurgical treatment process. This study aims to characterize the Mnore in Tanggamus and Way Kanan Regency Lampung Province and prospective process. Experiment begins with a sampling of the area in Tanggamus and Way Kanan mine. Sample preparation is then performed by reducing the particle size of the ore through the stages of crushing, grinding and particle size distribution. Mn ore sample which has been reduced then performed characterization using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). The results showed that the characteristics of Mn ore in Tanggamus and Way Kanan mine was different. Mn ore Tanggamus have the highest contentof 33.84% Mn associated with Fe2O3 minerals, while Mn ore Way Kanan had content 18.03% associated with SiO2 minerals. Both Mn ore are included in low grade Mn ore (<40). Prospective processing of manganese ore is initiated by benefitiation and proceed by leaching method.